The Effect of Cadmium Under Different Salinity Conditions on the Cellular Architecture and Metabolism in the Red Alga Pterocladiella capillacea (Rhodophyta, Gelidiales). (1st July 2014) - de L. Felix, Marthiellen R.; Osorio, Luz K.P.; Ouriques, Luciane C.; Farias-Soares, Francine L.; Steiner, Neusa; Kreusch, Marianne; Pereira, Debora T.; Simioni, Carmen; Costa, Giulia B.; Horta, Paulo A.; Chow, Fungyi; Ramlov, Fernanda; et al.
Abstract The in vitro effect of cadmium (Cd) on apical segments of Pterocladiella capillacea was examined. Over a period of 7 days, the segments were cultivated with the combination of different salinities (25, 35, and 45 practical salinity units) and Cd concentrations, ranging from 0.17 to 0.70 ppm. The effects of Cd on growth rates and content of photosynthetic pigments were analyzed. In addition, metabolic profiling was performed, and samples were processed for microscopy. Serious damage to physiological performance and ultrastructure was observed under different combinations of Cd concentrations and salinity values. Elementary infrared spectroscopy revealed toxic effects registered on growth rate, photosynthetic pigments, chloroplast, and mitochondria organization, as well as changes in lipids and carbohydrates. These alterations in physiology and ultrastructure were, however, coupled to activation of such defense mechanisms as cell wall thickness, reduction of photosynthetic harvesting complex, and flavonoid. In conclusion, P. capillacea is especially sensitive to Cd stress when intermediate concentrations of this pollutant are associated with low salinity values. Such conditions resulted in metabolic compromise, reduction of primary productivity, i.e., photosynthesis, and carbohydrate accumulation in the form of starch granules. Taken together, these findings improve our understanding of the potential impact of this metal in the natural environment.